2021
DOI: 10.3390/diagnostics11040681
|View full text |Cite
|
Sign up to set email alerts
|

Low Detection Rate of H3K27M Mutations in Cerebrospinal Fluid Obtained from Lumbar Puncture in Newly Diagnosed Diffuse Midline Gliomas

Abstract: Recent studies have suggested the feasibility of detecting H3K27M mutations in the cerebrospinal fluid of diffuse midline glioma (DMG) patients. However, cerebrospinal fluid from patients in these studies were collected mainly during biopsy, ventriculo-peritoneal shunt procedures or postmortem. We assessed circulating tumor DNA (ctDNA) extracted from cerebrospinal fluid (CSF) and plasma in a series of 12 radiographically suspected and/or pathologically confirmed diffuse midline glioma patients and assessed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…This situation reflects lower levels of wild-type positivity observed in dPCR with lumbar CSF-derived templates. We encountered two lumbar CSF samples from H3 K27M-positive DMG patients, similar to those described by On et al [ 23 ]—with low cfDNA concentrations and single positive signals in dPCR charts. For one of them, ventricular CSF was also available, and the result was interpreted unambiguously ( Figure 6 ).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This situation reflects lower levels of wild-type positivity observed in dPCR with lumbar CSF-derived templates. We encountered two lumbar CSF samples from H3 K27M-positive DMG patients, similar to those described by On et al [ 23 ]—with low cfDNA concentrations and single positive signals in dPCR charts. For one of them, ventricular CSF was also available, and the result was interpreted unambiguously ( Figure 6 ).…”
Section: Discussionsupporting
confidence: 61%
“…Despite the significantly reduced concentrations of cfDNA in CSF derived by lumbar puncture, Fujioka et al detected mutations in IDH1 , TERT , or H3 genes in six of seven high-grade glioma cases [ 22 ] . At the same time, On et al were able to unequivocally identify H3 K27M mutation in only 1 of 10 CSF samples obtained by lumbar puncture from newly diagnosed DMG patients; for three other cases in this cohort, the result was ambiguous, as only 1-2 mutant droplets were observed in ddPCR charts [ 23 ]. In our experience, concentrations of lumbar CSF-derived cfDNA (0–10, median 3 copies/µl) were also lower compared with the isolates obtained from ventricular CSF (0–15,170, median 94.5 copies/µl).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] About 50– 80% of these tumors carry mutations in the genes encoding histone 3, more specifically HIST1H3B (H3.1K27M) and H3F3A (H3.3K27M). [ 9 , 15 , 23 , 26 , 35 ] The discovery of such mutations brings hope for the development of new targeted therapies such as Impridone ONCO201 and IDO1 enzyme inhibitor which in preclinical trials have demonstrated activity against mutated H3K27M gliomas. [ 35 ] Through liquid biopsy of tumor DNA in CSF, we could diagnose such mutations, define the appropriate target therapies, and monitor the therapeutic response with the option of multiple throughout the disease course.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 , 15 , 20 ] On the other hand, studies using lumbar puncture to collect CSF resulted in a lower sensitivity for detection of tumor DNA when compared to the levels detected in samples collected through ventricular shunts. [ 23 ] Given the variety of diagnostic methods (Sanger, ddPCR, and NGS), biomarkers and collection methods used in the studies of this review, the need to standardize the steps for obtaining samples, analysis, and interpretation of results in liquid biopsy is evident.…”
Section: Discussionmentioning
confidence: 99%